2016
DOI: 10.1101/052076
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tumor evolution of glioma intrinsic gene expression subtype associates with immunological changes in the microenvironment

Abstract: SummaryWe leveraged IDH wild type glioblastomas and derivative neurospheres to define tumor-intrinsic transcription phenotypes. Transcriptomic multiplicity correlated with increased intratumoral heterogeneity and tumor microenvironment presence. In silico cell sorting demonstrated that M2 macrophages/microglia are the most frequent type of immune cells in the glioma microenvironment, followed by CD4 T lymphocytes and neutrophils. Hypermutation associated with CD8+ T cell enrichment. Longitudinal transcriptome … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 58 publications
5
33
1
Order By: Relevance
“…This phenomenon has been observed in 66 single cells in a HGSC tumor [87] and a subset of glioblastoma tumors by single cell profiling [88]. However, it has been recently shown that glioblastoma tumors are inherently heterogeneous by chance [89], and more single cell data is required to fully explore this phenomenon. Single cell RNAseq can reveal the types of cells in a complex mixture [90].…”
Section: Characteristics Of Hgsc Molecular Subtypesmentioning
confidence: 94%
“…This phenomenon has been observed in 66 single cells in a HGSC tumor [87] and a subset of glioblastoma tumors by single cell profiling [88]. However, it has been recently shown that glioblastoma tumors are inherently heterogeneous by chance [89], and more single cell data is required to fully explore this phenomenon. Single cell RNAseq can reveal the types of cells in a complex mixture [90].…”
Section: Characteristics Of Hgsc Molecular Subtypesmentioning
confidence: 94%
“…Despite this heterogeneity transcriptional profiling has identified tumor subtypes (1,2) with enrichment of specific cell signaling (3), proteomic (4,5) and immune cell characteristics (6,7). The design of improved therapeutics for GBM requires an understanding of intertumoral heterogeneity and its potential impact on therapeutic response.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular analyses comparing SFCs and ESCs sustained the notion that ESCs could be more dependent on exogenous stimuli. They formed a distinct subgroup in relation to the SFCs and were all assigned to the mesenchymal subtype, which has been demonstrated to have the highest influence of microenvironmental induced gene expression (Wang et al, ). ESCs continued to upregulate genes and pathways induced by exogenous stimuli also after being switched to SF culture conditions, which implied that they were derived from GBMs that were intrinsically different compared to those generating SFCs.…”
Section: Discussionmentioning
confidence: 99%
“…The raw data was RMA‐normalized using R‐library oligo (Carvalho & Irizarry, ). The SFC, ESC, and ESC_to_SFC samples were given subtype affiliations using ssGSEA analogous to the method as described previously (Wang et al, ). Hierarchical clustering was performed using R‐function hclust with complete linkage as an agglomeration method.…”
Section: Methodsmentioning
confidence: 99%